Routing algorithm based on location optimization of sink node in hybrid wireless sensor networks - Sai ZOU; Wen-yong WANG; Yong TANG; Jun ZHANG (Tongxin xuebao)
The data acquisition nodes in hybrid wireless sensor network usually suffer high energy consumption of data transmission and high ratio of packet loss. This issue is closely related to the position of data aggregation nodes (sink nodes) and can be improved by optimizing the location of these nodes. It was adopted in the routing algorithm based on location optimization of mobile sink nodes (MLOYIH). In MLOYIH, ant colony algorithm was used to divide the mobile nodes and static nodes into groups and then the suitable positions of the aggregation nodes were determined within each group. Then the suitable networking routing was established according to the power supply of sensor nodes. Simulation shows that MLOYIH algorithm has a lower energy consumption with a reduction of 64% compared with the traditional algorithms, and the ratio of packet loss is less than 3%.